2022
DOI: 10.1007/s00251-021-01249-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic evolution of Mhc haplotypes in cynomolgus macaques of different geographic origins

Abstract: The major histocompatibility complex (MHC) plays a key role in immune defense, and the Mhc genes of cynomolgus macaque display a high degree of polymorphism. Based on their geographic distribution, different populations of cynomolgus macaques are recognized. Here we present the characterization of the Mhc class I and II repertoire of a large pedigreed group of cynomolgus macaques originating from the mainland north of the isthmus of Kra ( N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…There is no reason to believe that the Indonesian cynomolgus macaque sequenced for the Macaca_ fascicularis_5.0 assembly would not have a similar MHC class I gene density as the cy0333 M3 haplotype of MCM. Mauritian cynomolgus macaques are most likely derived from a small population of Indonesian cynomolgus macaques, and previous MHC haplotyping studies of cynomolgus macaques from Indonesia as well as other geographic origins have shown expected levels of segmental duplications for these regions (Shortreed et al 2020; de Groot et al 2022). However, the MHC class I A and class I B regions for Macaca_fascicularis_5.0 are both significantly shorter than their cy0333 counterparts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no reason to believe that the Indonesian cynomolgus macaque sequenced for the Macaca_ fascicularis_5.0 assembly would not have a similar MHC class I gene density as the cy0333 M3 haplotype of MCM. Mauritian cynomolgus macaques are most likely derived from a small population of Indonesian cynomolgus macaques, and previous MHC haplotyping studies of cynomolgus macaques from Indonesia as well as other geographic origins have shown expected levels of segmental duplications for these regions (Shortreed et al 2020; de Groot et al 2022). However, the MHC class I A and class I B regions for Macaca_fascicularis_5.0 are both significantly shorter than their cy0333 counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…The full genomic MHC region of Macaca_fascicularis_5.0 is also notably over 1.3 Mb shorter than macaques from Indonesia as well as other geographic origins have shown expected levels of segmental duplications for these regions (Shortreed et al 2020;de Groot et al 2022). However, the MHC class I A and class I B regions for Macaca_fascicularis_5.0 are both significantly shorter than their cy0333 counterparts.…”
Section: Comparison To the Mhc Region Of Other Macaque Reference Genomesmentioning
confidence: 94%
“…One to two major transcribed and up to five minor transcribed Mafa-A genes may be detected per haplotype [ 93 97 ]. A haplotype can comprise one to seven major transcribed and up to fifteen minor transcribed Mafa-B genes [ 93 97 ]. Our data illustrated that the number of Mafa-A and Mafa-B genes varies among haplotypes in this assembled cynomolgus macaque genome.…”
Section: Discussionmentioning
confidence: 99%
“…Mamu-B*017:01 controls SIV replication and disease progression [ 26 ]. The B1, B4, and B9 genes were reported to have low transcription levels [ 93 97 ], and only three alleles ( Mafa-B*180:02:01:02nov, Mafa-B*124:03:01:01nov, Mafa-B*021:07nov ) were detected in the B9 locus. The combinations I*01-B*056:05-B*034:04 (animal 1, 5, 6, 18, 21) and I*01-B*034:04-B11L*01 (animal 16) matched the Mafa-B region in contig utg000348l.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation